Sistem layanan pendidikan anak berbakat Di SMA Negeri khusus Jeneponto - Rosbiah, Rosbiah (Universitas Negeri Makassar, 2017)
The purpose of this study is to investigate the implementation of the education service system that is applied in SMA Special Jeneponto include: differentiated curriculum, methods, strategies and models the learning, facilities and infrastructure, teacher qualifications as well as guidance and counseling services for gifted children. This study uses a qualitative approach with case studies. Purposively selected data sources with data collection through interviews (depth interview), observation and documentation. Data were analyzed through data reduction, data presentation, data verification and conclusion. The results showed that the system of education of gifted children in SMA Special Jeneponto can be concluded that: (i) using curriculum differentiation, (ii) using the methods of learning centered on the student, (iii) the facilities and infrastructure there are simply not enough, (iv ) qualified teacher is dedicated teachers and instructors, (v) guidance and counseling given to gifted children to help students discover and develop special talents in accordance with the potential and capabilities they have.